On the Stream Function-Vorticity Finite Element Formulation for Incompressible Flow in Porous Media. (18th September 2014) - Agouzal, Abdellatif; Allali, Karam; Binna, Siham
Abstract : Stream function-vorticity finite element formulation for incompressible flow in porous media is presented. The model consists of the heat equation, the equation for the concentration, and the equations of motion under the Darcy law. The existence of solution for the discrete problem is established. Optimal a priori error estimates are given.